Penerapan Metode Drill untuk Meningkatkan Hasil Belajar Passing Bawah Bola Voli Siswa Kelas V Sekolah Dasar - Partini, Partini (Universitas Sebelas Maret, 2018)
Abstract. The purpose of this study was to find out the application of the drill method in improving the results of volleyball under-passing learning of fifth grade students of Mlese 1 Elementary School in Klaten Regency, Semester I 2018/2019 Academic Year. The research subjects consisted of 18 students. The instrument used to measure the success of teacher and student activities in teaching and learning activities is by using an observation sheet, while measuring student learning outcomes is a cognitive, affective and psychomotor test. Thisresearch was conducted in two cycles. The stages in this study follow the procedure of classroom action research, namely: (1) planning, (2) implementation of actions, (3) observations, and (4) reflection. From the results of the study concluded that the activities and learning outcomes of fifth grade students of SD Negeri 1 Mlese Gantiwarno District, Klaten Regency using the drill method showed maximum results, where in the first cycle the completeness level of teacher activities in carrying out learning activities only reached 72.72%and increased in cycle II to 100%, for student learning completeness data 70% and experienced an increase in cycle II to 90%, this has exceeded standards based on minimum completeness criteria of 85%. While the learning outcomes of students in the first cycle only reached 66.67%, increasing in the second cycle to 94.44% or have reached the level of learning completeness set by the school which is 80%. Thus it can be concluded that the application of the drill method can improve the results of volleyball under-passing learning in grade V students of SD Negeri 1 Mlese Gantiwarno District, Klaten Regency, first semester of the school year 2018/2019.